Design and numerical evaluation of a volume coil array for parallel MR imaging at ultrahigh fields - Pang, Yong; Wong, Ernest W.H.; Yu, Baiying; Zhang, Xiaoliang (Quantitative Imaging in Medicine and Surgery, 2014)
In this work, we propose and investigate a volume coil array design method using different types of birdcage coils for MR imaging. Unlike the conventional radiofrequency (RF) coil arrays of which the array elements are surface coils, the proposed volume coil array consists of a set of independent volume coils including a conventional birdcage coil, a transverse birdcage coil, and a helix birdcage coil. The magnetic fluxes of these three birdcage coils are intrinsically cancelled, yielding a highly decoupled volume coil array. In contrast to conventional non-array type volume coils, the volume coil array would be beneficial in improving MR signal-to-noise ratio (SNR) and also gain the capability of implementing parallel imaging. The volume coil array is evaluated at the ultrahigh field of 7T using FDTD numerical simulations, and the g-factor map at different acceleration rates was also calculated to investigate its parallel imaging performance.